The potential regulatory role of the lncRNA-miRNA-mRNA axis in teleost fish - Zhou, Zhixia; Leng, Cuibo; Wang, Zhan; Long, Linhai; Lv, Yiju; Gao, Ziru; Wang, Yin; Wang, Shoushi; Li, Peifeng (Frontiers in Immunology, 2023)
Research over the past two decades has confirmed that noncoding RNAs (ncRNAs), which are abundant in cells from yeast to vertebrates, are no longer “junk” transcripts but functional regulators that can mediate various cellular and physiological processes. The dysregulation of ncRNAs is closely related to the imbalance of cellular homeostasis and the occurrence and development of various diseases. In mammals, ncRNAs, such as long noncoding RNAs (lncRNAs) and microRNAs (miRNAs), have been shown to serve as biomarkers and intervention targets in growth, development, immunity, and disease progression. The regulatory functions of lncRNAs on gene expression are usually mediated by crosstalk with miRNAs. The most predominant mode of lncRNA-miRNA crosstalk is the lncRNA-miRNA-mRNA axis, in which lncRNAs act as competing endogenous RNAs (ceRNAs). Compared to mammals, little attention has been given to the role and mechanism of the lncRNA-miRNA-mRNA axis in teleost species. In this review, we provide current knowledge about the teleost lncRNA-miRNA-mRNA axis, focusing on its physiological and pathological regulation in growth and development, reproduction, skeletal muscle, immunity to bacterial and viral infections, and other stress-related immune responses. Herein, we also explored the potential application of the lncRNA-miRNA-mRNA axis in the aquaculture industry. These findings contribute to an enhanced understanding of ncRNA and ncRNA-ncRNA crosstalk in fish biology to improve aquaculture productivity, fish health and quality.